Hybrid neuromuscular training promotes musculoskeletal adaptations in inactive overweight and obese women: A training-detraining randomized controlled trial. Issue 5 (4th March 2021) - Batrakoulis, Alexios; Tsimeas, Panagiotis; Deli, Chariklia K.; Vlachopoulos, Dimitrios; Ubago-Guisado, Esther; Poulios, Athanasios; Chatzinikolaou, Athanasios; Draganidis, Dimitrios; Papanikolaou, Konstantinos; Georgakouli, Kalliopi; Batsilas, Dimitrios; Gracia-Marco, Luis; et al.
ABSTRACT: This study investigated the effects of a 10-month high-intensity interval-type neuromuscular training programme on musculoskeletal fitness in overweight and obese women. Forty-nine inactive females (36.4 ± 4.4 yrs) were randomly assigned to either a control (N = 21), a training (N = 14, 10 months) or a training-detraining group (N = 14, 5 months training followed by 5 months detraining). Training used progressive loaded fundamental movement patterns with prescribed work-to-rest intervals (1:2, 1:1, 2:1) in a circuit fashion (2–3 rounds). Muscular strength and endurance, flexibility, passive range of motion (PRoM), static balance, functional movement screen (FMS) and bone mass density (BMD) and content (BMC) were measured at pre-, mid-, and post-intervention. Ten months of training induced greater changes than the controls in (i) BMD (+1.9%, p < 0.001) and BMC (+1.5%, p = 0.023) ii) muscular strength (25%-53%, p = 0.001–0.005); iii) muscular endurance (103%-195%, p < 0.001); and iv) mobility (flexibility: 40%, p < 0.001; PRoM [24%-53%, p = 0.001–0.05;]; balance: 175%, p = 0.058; FMS: +58%, p < 0.001). The response rate to training was exceptionally high (86–100%). Five months of detraining reduced but not abolished training-induced adaptations. These results suggest that a hybrid-type exercise approach integrating endurance-based bodyweight drills with resistance-based alternative modes into a real-world gym setting may promote musculoskeletal fitness in overweight and obese women.